1999
DOI: 10.1038/sj.leu.2401466
|View full text |Cite
|
Sign up to set email alerts
|

Distinct genetic involvement of the TP53 gene in therapy-related leukemia and myelodysplasia with chromosomal losses of Nos 5 and/or 7 and its possible relationship to replication error phenotype

Abstract: We examined chromosomes and molecular aberrations in 21 patients with therapy-related leukemias (t-AML) or myelodysplastic syndromes (t-MDS). All patients showed abnormal karyotypes, and chromosomal losses of No. 5 and/or No. 7 (−5/5q− and/or −7/7q−) were identified in 12 patients. Among these 12, six patients (50%) harbored a TP53 mutation, and two of five examined showed microsatellite instability, suggesting replication error (RER ؉ ) phenotype. Meanwhile, among the other nine patients without −5/5q− and/or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 32 publications
4
45
0
Order By: Relevance
“…Independent of the state of complexity, there were significant higher amounts of CD34 þ cells. Published in vitro investigations 27,28 indicated that the loss of p53 function could cause cell-cycle arrest in a very primitive stage of 14,21,29,30 Furthermore, we could see an inverse correlation between p53 deletion and the molecular risk factors FLT3-ITD and NPM1 mutation.…”
Section: Discussionmentioning
confidence: 51%
“…Independent of the state of complexity, there were significant higher amounts of CD34 þ cells. Published in vitro investigations 27,28 indicated that the loss of p53 function could cause cell-cycle arrest in a very primitive stage of 14,21,29,30 Furthermore, we could see an inverse correlation between p53 deletion and the molecular risk factors FLT3-ITD and NPM1 mutation.…”
Section: Discussionmentioning
confidence: 51%
“…5 On the other hand, patients belonging to pathway II frequently present a complex karyotype and a mutation of p53, whereas pathway I has a very low frequency of p53 mutations. 22,34 However, we have focused on the pivotal role of AML1 mutations, rather than cytogenetic abnormalities, during the development of MDS/AML. We are trying to define the disease entity of 'MDS/AML with AML1 mutation', which could be considered for inclusion in the recurrent genetic abnormalities under the WHO classification.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of therapy-related AML/ MDS found p53 mutations in 30% of cases, with the majority of the mutated samples showing a loss of the wild type p53 allele (Horiike et al, 1999;Christiansen et al, 2001). In two studies involving 351 patient samples of AML and MDS (Fenaux et al, 1991;, 38 of 59 samples (64%) that showed a deletion of chromosome 17p had a point mutation of the remaining p53 allele.…”
Section: Ink4 Family Of Proteinsmentioning
confidence: 99%